A ghost in the machine? The predictive role of metacognitive beliefs, cognitive biases, and machine-related features in the severity of problematic slot machine gambling. (March 2021) - Moritz, Steffen; Gehlenborg, Josefine; Bierbrodt, Julia; Wittekind, Charlotte E.; Bücker, Lara
Abstract: Slot machine gambling is considered the most addictive form of gambling. The present study explored the predictive role of beliefs and cognitive biases as well as machine-related features in gambling severity. An online survey was conducted in 265 individuals with slot machine-related gambling problems. Gambling severity was assessed with the Pathological Gambling Yale-Brown Obsessive-Compulsive Scale. We also administered scales assessing false beliefs pertaining to gambling, including self-developed questionnaires tapping beliefs specific to slot machine gambling and the addictive properties of features related to the machines themselves. The desire to win and to chase lost money and the seeking of positive emotions were endorsed by the majority of participants and were correlated with the severity of gambling. Superstitious beliefs were also frequently endorsed. Slot machine-related features deemed most addictive by gamblers were pictures and sounds. Surprisingly, illusion of control was rarely endorsed and was uncorrelated with gambling severity. Winning and chasing (lost) money and seeking of positive emotions were endorsed by most slot machine gamblers and were associated with gambling severity. In view of empirical support for a metacognitive training for gamblers, we recommend not only conveying disorder-related dysfunctional beliefs to gamblers but also demonstrating and challenging them through behavioral experiments.